2019
DOI: 10.1016/j.ifacol.2019.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Determinant strategies in finitely repeated n-player games

Abstract: In two-player repeated games, Zero-Determinant (ZD) strategies are a class of strategies that can enable a player to unilaterally enforce a linear payoff relation between her own and her opponent's payoff irrespective of the opponent's strategy. This manipulative nature of the ZD strategies attracted significant attention from researchers due to its close connection to controlling distributively the outcome of evolutionary games in large populations. In this paper, we study the existence of ZD strategies in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Our results are limited to the two player RPD games. Other studies have focused on n-player games [19,26,27,56]. It is worth investigating games including observation errors and a discount factor for n-player games .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are limited to the two player RPD games. Other studies have focused on n-player games [19,26,27,56]. It is worth investigating games including observation errors and a discount factor for n-player games .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our results are limited to the two-player RPD games. Other studies have focused on n-player games [19,30,33,34]. Investigating the conditions for the existence of ZD strategies in n-player games warrant future work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, we use the framework of ZD strategies in infinitely repeated multiplayer social dilemmas from [9] and extend it to the case in which future payoffs are discounted with a fixed and common discount factor, or equivalently, to a repeated game with a finite expected number of rounds. We then build upon our results in [4], in which enforceable payoff relations were characterized, by developing new theory that allows us to express threshold discount factors that determine how fast a desired linear payoff relation can be enforced in a multiplayer social dilemma game. These results extend the work of [11] to a broad class of multiplayer social dilemmas.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is quite natural to incorporate a discount factor into the model. Some studies have revealed the existence of ZD strategies with a discount factor [26,27,[35][36][37]. Hence, in this study, we incorporate a discount factor into the model and explore whether the opponent is led to an unconditional cooperation.…”
Section: Introductionmentioning
confidence: 99%